Control of Post-harvest Citrus Green Mold using Ulva lactuca Extracts as a Source of Active Substances - Salim, D.; Caro, P. de; Merah, O.; Chbani, A. (International Journal of Bio-resource and Stress Management, 2020)
Penicillium digitatum, the causal agent of citrus green mold, is responsible for 90% of post-harvest losses. Chemical fungicides are responsible for damage to human health and the environment. The exploitation of green algae as a source of pigments and carbohydrate polymers deserves a special attention. In this study, we evaluated the ability of Ulva lactuca extracts collected from Lebanon and China, to develop products for the biocontrol of post-harvest citrus green mold. Seaweed aqueous extracts (SAE), organic extracts (SOE) and chlorophylls and Ulvans fractions of Ulva lactuca are analyzed by chromatography and spectroscopy methods. The chemical compositions in functional molecules (pigments, organic acids, and monosaccharides) from extracts are compared for the samples. It was found that Lebanese Ulva lactuca is particularly rich in ulvans and other polysaccharides, while Food grade Ulva lactuca has the highest content in lipophilic molecules. Four approaches were used to evaluate their antifungal properties: inhibition of the conidia germination of P. digitatum, fungus viability, adhesion of spores to epidermal orange cells, and the disk diffusion method. For the different seaweed liquid extracts (SLEs), inhibitions of spore germination were observed between 70 and 87%. Moreover, the samples exhibited inhibitory activities towards the adhesion of P. digitatum spores. More particularly, SOE showed inhibitions of spore multiplication between 85 and 97%. According zone diamaters, Ulvan fractions showed maximum growth spore inhibitions. These findings are interesting to select extracts for safe and effective formulations dedicated to citrus fruit post harvesting protection.